33% Giant Anomalous Hall Current Driven by Both Intrinsic and Extrinsic Contributions in Magnetic Weyl Semimetal Co3Sn2S2. (25th June 2020) - Shen, Jianlei; Zeng, Qingqi; Zhang, Shen; Sun, Hongyi; Yao, Qiushi; Xi, Xuekui; Wang, Wenhong; Wu, Guangheng; Shen, Baogen; Liu, Qihang; Liu, Enke
Abstract: The anomalous Hall effect (AHE) can be induced by intrinsic mechanisms due to the band Berry phase and extrinsic one arising from the impurity scattering. The recently discovered magnetic Weyl semimetal Co3 Sn2 S2 exhibits a large intrinsic anomalous Hall conductivity (AHC) and a giant anomalous Hall angle (AHA). The predicted energy dependence of the AHC in this material exhibits a plateau at 1000 Ω −1 cm −1 and an energy width of 100 meV just below E F, thereby implying that the large intrinsic AHC will not significantly change against small‐scale energy disturbances such as slight p‐ doping. Here, the extrinsic contribution is successfully triggered from alien‐atom scattering in addition to the intrinsic one of the pristine material by introducing a small amount of Fe dopant to substitute Co in Co3 Sn2 S2 . The experimental results show that the AHC and AHA can be prominently enhanced up to 1850 Ω −1 cm −1 and 33%, respectively, owing to the synergistic contributions from the intrinsic and extrinsic mechanisms as distinguished by the TYJ model. In particular, the tuned AHA exhibits a record value among known magnetic materials in low fields. This study opens up a pathway to engineer giant AHE in magnetic Weyl semimetals, thereby potentially advancing the topological spintronics/Weyltronics. Abstract : Due to the prominent contribution of both the intrinsic and extrinsic Hall mechanisms, significantly enhanced AHC (≈1850 Ω −1 cm −1 ) and AHA (≈33%) are obtained at the zero field in the magnetic Weyl semimetal Co3 Sn2 S2 by controlling slight Fe doping. In comparison with other AHE materials, the AHC and AHA for Co3– x Fe x Sn2 S2 exhibit record values, which can greatly benefit Weyltronics applications.